Pengaruh Nilai Kerja Terhadap Kinerja Karyawan - Pantouw, Yuvika Monika; Tatimu, Ventje; Sambul, Sofia A. P. (Sam Ratulangi University, 2019)
The purpose of this study was to determine the effect of work value on the performance of study employees in Millennial Bank Mandiri Area Manado employees. Values contain an element of judgment because they contain an individual's ideas about what is true, good or desirable. Work values are important for studying organizational behavior because work values are the basis for understanding attitudes and motivation and influencing our perception. Performance is the result or results achieved during a certain period in the tasks compared to, such as work standards, targets or goals or criteria that have been agreed upon in advance have been agreed upon. The relationship between work values and employee performance is closely related to employee empowerment in a company. The analytical method used is a simple linear regression analysis. The results of this study stated that the Value variable in this study had a positive and significant effect on Employee Performance in the Study of millennial generation employees in Bank Mandiri Area Manado.PT. Bank Mandiri in Manado should increase and pay more attention to the value of work than employees within the company, especially to millennial generation employees, because giving due to paying attention to work values than millennial generation employees can improve employee performance within the company.